4-Chlorothymol Exerts Antiplasmodial Activity Impeding Redox Defense System in Plasmodium falciparum - Kumar, Saurabh; Mina, Pooja Rani; Kumar, Ravi; Pal, Anirban; Ahmad, Ateeque; Tandon, Sudeep; Darokar, Mahendra P. (Frontiers in Pharmacology, 2021)
Malaria remains one of the major health concerns due to the resistance of Plasmodium species toward the existing drugs warranting an urgent need for new antimalarials. Thymol derivatives were known to exhibit enhanced antimicrobial activities; however, no reports were found against Plasmodium spp. In the present study, the antiplasmodial activity of thymol derivatives was evaluated against chloroquine-sensitive (NF-54) and -resistant (K1) strains of Plasmodium falciparum. Among the thymol derivatives tested, 4-chlorothymol showed potential activity against sensitive and resistant strains of P. falciparum. 4-Chlorothymol was found to increase the reactive oxygen species and reactive nitrogen species level. Furthermore, 4-chlorothymol could perturb the redox balance by modulating the enzyme activity of GST and GR. 4-Chlorothymol also showed synergy with chloroquine against chloroquine-resistant P. falciparum. 4-Chlorothymol was found to significantly suppress the parasitemia and increase the mean survival time in in vivo assays. Interestingly, in in vivo assay, 4-chlorothymol in combination with chloroquine showed higher chemosuppression as well as enhanced mean survival time at a much lower concentration as compared to individual doses of chloroquine and 4-chlorothymol. These observations clearly indicate the potential use of 4-chlorothymol as an antimalarial agent, which may also be effective in combination with the existing antiplasmodial drugs against chloroquine-resistant P. falciparum infection. In vitro cytotoxicity/hemolytic assay evidently suggests that 4-chlorothymol is safe for further exploration of its therapeutic properties.